2012
DOI: 10.1002/glia.22421
|View full text |Cite
|
Sign up to set email alerts
|

Complex invasion pattern of the cerebral cortex bymicroglial cells during development of the mouse embryo

Abstract: Microglia are the immune cells of the central nervous system. They are suspected to play important roles in adult synaptogenesis and in the development of the neuronal network. Microglial cells originate from progenitors in the yolk sac. Although it was suggested that they invade the cortex at early developmental stages in the embryo, their invasion pattern remains largely unknown. To address this issue we analyzed the pattern of cortical invasion by microglial cells in mouse embryos at the onset of neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(247 citation statements)
references
References 59 publications
8
226
0
5
Order By: Relevance
“…1a,b), at E14.5, E16.5 and E18.5 such cells were preferentially clustered into the VZ/SVZ of the cerebral cortex ( Supplementary Fig. 1a-c) 15 . Because microglia cell number significantly increased along neurogenesis in cortical and subcortical areas (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1a,b), at E14.5, E16.5 and E18.5 such cells were preferentially clustered into the VZ/SVZ of the cerebral cortex ( Supplementary Fig. 1a-c) 15 . Because microglia cell number significantly increased along neurogenesis in cortical and subcortical areas (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…9) to promote the development of Cajal-Retzius cells 49 -are not affected in our mutant mice, thus suggesting that they might per se contribute to attract circulating microglia. Owing to the fact that B20% of the mid-end gestational cortical microglia is actively proliferating 15 , we cannot exclude that cell proliferation represents a rescue mechanism aimed at balancing microglia depletion occurring as a consequence of Cxcl12 reduction. Apart from the existence of additional sources of Cxcl12 in the developing brain, we cannot rule out the possibility of the existence in the developing brain of microglia progenitors, able to proliferate in order to replenish the microglia cell pool as occurs in pathological conditions determining microglia depletion in the adult brain 50 .…”
Section: E145mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, electrophysiological studies in mouse cortex have revealed that the population of early postnatal microglia presents a transient outward rectifying current above -30mV mediated by Kv1.3 potassium channels, similar to activated microglia, however, these postnatal microglia do not express other known activation markers like Mac2 or MHCII 12 . Additionally, these microglial cells also express a panel of specific markers including purinergic receptors 10,12 . The mouse retinogeniculate system is a classic model for studying developmental synapse elimination.…”
Section: Introductionmentioning
confidence: 99%
“…De telles études ont pu être mises en oeuvre grâce à l'utilisation d'anticorps spécifiques dirigés contre des protéines exprimées par les cellules microgliales, et surtout grâce à la production de souris exprimant la eGFP (enhanced green fluorescent protein, une protéine fluorescente) dans les cellules microgliales (souris CX 3 CR1eGFP) [9]. Chez la souris, les cellules microgliales envahissent la moelle épi-nière (ME) et le cerveau au même âge embryonnaire [10,11]. Des macrophages immatures sont observés autour du parenchyme neural vers le 9,5 e -10,5 e jour après la fertilisation (E9,5-E10,5), qui forment probablement un réservoir de cellules microgliales.…”
Section: Les Cellules Microgliales Envahissent Le Snc à Des Stades Prunclassified